Evaluation of serum levels of irisin, tumor necrosis factor and some biochemical variables in males with prostate cancer in Baghdad City: Irisin, tnf, and biochemical variables in prostate cancer - Hanan Shihab Ahmad,; Abdulwahed, Araf Sabah; Kamil, Marwan Abdulrazzaq (Cellular and Molecular Biology, 2025)
Prostate cancer is the most common type after the age of fifty. It affects males and affects the prostate gland, which protects the function of sperm by producing semen. The current study was designed to evaluate prostate cancer infection effects on some biomarkers such as irisin, Tumor necrosis factor-TNF-α, prostate acid phosphates -PAP, Glutathione-GSH, malondialdehyde-MDA, urea, and creatinine. The study was conducted on 50 males infected with prostate cancer and 30 healthy males (control group) who attended the Baghdad Teaching Hospital –Medical City Center/Baghdad, Iraq, from 20/6/2024 to 1/8/2024. The results of the current research showed a significant elevation in (Irisin, TNF-α, PAP, MDA, urea, and creatinine) concentration and a significant decrease in (GSH) concentration in the serum of patients compared to the healthy subjects in the probability of P≤0.05. Irisin and some variables are important physiological biomarkers that can support the diagnosis of prostate cancer.